(untitled) (Trabalho & Educação, 2018)
The research entitled “Comparative Study on School Dropout in Vocational Education - Brazil and Argentina” deals with the problem of school dropout in technical secondary education and it is part of the production of the Iberoamerican Network of Studies on Vocational Education and School Dropout (RIMEPES). As the network research shows, it is necessary to study the systemic factors related to dropout, identifying peculiarities of legislation, public policies and educational programs in each context in order to combat the school dropout. The general objective of this thesis is to analyze the systemic factors related to school dropout in Brazil and Argentina in a comparative way. To this end, as specific objectives, the national education systems of both countries are described, the historical frameworks that made up both educational systems are analyzed, and public policies and programs aimed at combating school dropout in education are described. Specifically, in the Brazilian case, it was analyzed the initiatives of the Secretariat of Vocational and Technological Education (SETEC) of the Ministry of Education, aimed at the Federal Network of Vocational, Scientific and Technological Education (RFEPT). In the Argentine case, the initiatives coordinated by the National Institute of Technological Education (INET) of the Ministry of Education were aimed at secondary technical schools. It is considered that for both cases... ___ A pesquisa doutoral “Estudo Comparado sobre Evasão Escolar na Educação Profissional - Brasil e Argentina” aborda o problema da evasão escolar no ensino médio técnico e se insere no contexto de produção da Rede Ibero-Americana de Estudos sobre Educação Profissional e Evasão Escolar (RIMEPES). Como suas pesquisas demonstram, revelou-se necessário considerar os fatores sistêmicos relacionados à evasão, de modo a identificar peculiaridades da legislação, das políticas públicas e dos programas educacionais vigentes direcionadas para o combate à evasão. O objetivo geral da tese consistiu em analisar, de forma comparada, os fatores sistêmicos relacionados à evasão escolar no ensino médio técnico no Brasil e na Argentina. Como objetivos específicos, apontam-se: descrever os sistemas de educação de ambos os países; analisar os marcos históricos que compuseram ambos os sistemas educativos e descrever as políticas públicas e os programas destinados a combater a evasão escolar dos estudantes no ensino médio técnico entre 2003 e 2015. Para o caso brasileiro, analisaram-se as iniciativas da Secretaria de Educação Profissional e Tecnológica (SETEC) do Ministério da Educação, dirigidas à Rede Federal de Educação Profissional, Científica e Tecnológica (RFEPT); e, para o argentino, aquelas coordenadas pelo Instituto Nacional de Educação Tecnológica (INET), do Ministério da Educação, dirigidas às escolas técnicas estatais de nível secundário. Apurou-se que para ambos os casos...